Vulvar mastocytosis. - Garofalo, L. (European Journal of Pediatric Dermatology, 2009)
A 40-day-old baby girl was first observed due to two hemangiomas that progressively regressed in the subsequent years. When aged 3 years she presented macular and papular lesion on the scalp. One of the latter gave rise to a serous blister that spontaneously regressed. In the subsequent months multiple lesions appeared on her trunk leading to the final diagnosis of mastocytosis. At the age of 3 1/2 years a papule appeared on her vulvar region and in the subsequent months other 2 smaller papules appeared close to the first one. We considered the diagnosis of virus papillomas, adnexal and histiocytic tumors. At the age of 6 years the largest -3 mm in size-, yellowish papule (Fig. 1) with smooth surface and hard elastic consistency was removed. The histological diagnosis (Fig. 2, 3) was vulvar mastocytosis.